1996
DOI: 10.1590/s1516-31801996000400007
|View full text |Cite
|
Sign up to set email alerts
|

Arterial embolectomy in lower limbs

Abstract: Arterial embolisms in the lower limbs occur frequently, and are of great interest to the vascular surgeon. The authors studied 159 cases of arterial embolisms in lower limbs from January 1991 to July 1993. Ages varied from 12 to 98, with a mean of 58. Eighty patients were male and 78 were female. In most cases, etiology of the embolus was well-established, and mainly caused (78 percent) by atrial fibrillation. Occlusion was most frequent in the femoral artery (53.4 percent). All patients presented severe lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
1
5
0
1
Order By: Relevance
“…Although ALI can be treated up to 14 days after injury, early intervention reduces tissue damage and improves success [39]. Interventions within 24 h has good outcomes [40,41]. In our study, we have seen the same outcomes.…”
Section: Discussionsupporting
confidence: 70%
“…Although ALI can be treated up to 14 days after injury, early intervention reduces tissue damage and improves success [39]. Interventions within 24 h has good outcomes [40,41]. In our study, we have seen the same outcomes.…”
Section: Discussionsupporting
confidence: 70%
“…The degree of ischemic involvement is always higher in the lower extremities because of poor collateral circulation. Wolosker et al [1996] investigated the effect of surgery on embolism but did not consider the duration of ischemia. Limb amputation occurred in 16.4% of the surviving patients (versus 13.7% in our study).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15 to 20 percent of patients die within one year of presentation of their limb ischemia, usually from the medical illnesses that predispose them to acute limb ischemia. 1,8,9 Most of the studies reported the risk factors associated with 30-days and 1-year mortality. The data on factors that contribute to in-hospital mortality is currently lacking.…”
Section: Discussionmentioning
confidence: 99%